The Ngee Ann Kongsi and Singapore Management University partner to promote research on elderly well-being - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
The Ngee Ann Kongsi intends to support SMU with $15 million over seven years, which will be SMU’s largest non-government research funding to date.